Journal Review: Formulation and Evaluation of Anti-Oxidant Facial Serum and From Extracts of Various Plants - Kandida Hilda Novika; Anis Yohana Chaerunissa; Sriwidodo Sriwidodo; Widia Primi Annissya (Eduvest - Journal of Universal Studies, 2024)
In the 19th century, the use of cosmetics began to gain attention, not only for beauty but also for health. Facial serum is a skin care product in the form of a gel or light lotion with a moisturizer that contains active ingredients that can penetrate deeper into the skin. UV rays can damage collagen/elastin in the skin, cause hyperpigmentation, damage skin components and trigger premature aging. So, antioxidants are needed to ward off free radicals. The main function of antioxidants is to capture and neutralize free radicals thereby reducing or preventing damage. The aim of this literature review is to provide information and evaluate the effectiveness of facial serums formulated from various extracts that have the potential to act as antioxidants. The method used in this literature review is using a data base in the form of Google Scholar, Pubmed, Pharmaceuticals, and Science Direct (2015-2023). Based on the results of the literature review, 55 journals were found with various types of plants as antioxidants all types of plants which has antioxidant activity in serum preparations which is classified as very strong is Mangosteen Fruit Extract (Garcinia Mangostana) with an IC50 value of 5-15 μg/mL.